Defining of EAF steel slag application possibilities in asphalt mixture production - Sofilic, Tahir; Mladenovič, Ana; Sofilič, Una (Journal of Environmental Engineering and Landscape Management, 2011)
Electric arc furnace (EAF) steel slag, generated from carbon steel production process, is the most interesting from the asphalt technology point of view. This paper aims to explore the feasibility of utilizing steel slag as aggregates in asphalt mixtures. Characterization of EAF slag was carried out through examination of its physical and chemical properties with special emphasis on chemical and structural characteristics. Optical Microscopy (OM), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectrometry (EDS) and γ-spectrometric analysis were employed to study the texture, morphology and composition of steel slag. Volume properties of steel slag were also evaluated as compared to those of natural aggregates. For this purpose the specimens of EAF slag were taken from the regular production processes in CMC Sisak, Croatia, Steel mill. The results which were obtained by testing geometric, physicalmechanic properties, as well as the properties of duration on the specimen of electric furnace steel slag of CMC Sisak, when compared to steel slag properties of other steel producers (Acroni, Jesenice, Slovenia and Štore Steel, Štore, Slovenia) and with properties of natural aggregates, have satisfied the conditions for manufacturing mixtures of the tested steel slag and natural stone, which can be used in asphalt production. In comparison to the natural aggregates, which are used in asphalt mixtures on highways and roads with heavy traffic, the examined steel slag has equally good physical and mechanical properties, while it is significantly better when it comes to resistance to polishing. Special attention has been given to the free CaO and free MgO, which can cause volume instability, thus limiting the use of steel slag in road construction. Article in English. Elk plieno šlako panaudojimo gaminant asfalto mišinį galimybės Santrauka. Nagrinėjamos plieno šlako panaudojimo asfalto mišiniui gaminti galimybės. Šis šlakas susidaro elektros lanko krosnyje (ELK) anglies plieno gamybos procese. Nagrinėjamos fizikinės bei cheminės šlako savybės, pateikiamos cheminės ir struktūrines charakteristikos. Plieno šlako tekstūra, morfologija ir sudėtis nustatyta taikant optinę mikroskopiją (OM), rentgeno spindulių difrakciją (RSD), skenuojančiąją elektroninę mikroskopiją (SEM), energijos dispersinę spektrometriją (EDS) bei spektrometrinę analizę. ELK šlako mėginiai buvo paimti iš plieno gamyklos CMC Sisak, Kroatijoje. Šių mėginių geometrinės, fizikinės ir mechaninės bei patvarumo savybės buvo lyginamos su kitų šlakų (Acroni, Jesenice, Slovenija ir Store steel, Štore, Slovėnija) ir natūralių agregatų savybėmis. Gauti rezultatai patvirtino tirto plieno šlako bei natūralaus akmens panaudojimo gaminant asfaltą galimybes. Natūralūs agregatai, naudojami asfalto mišiniuose tiesiant greitkelius ir intensyvaus eismo kelius, bei tiriamas plieno šlakas turi panašių gerų fizikinių bei mechaninių savybių, tačiau ELK šlakas yra atsparesnis gludinimui. Daug dėmesio buvo skirta laisviesiems CaO ir MgO, lemiantiems medžiagos nepatvarumą. Šie oksidai yra pagrindinis veiksnys, ribojantis plieno šlako naudojimą asfaltui gaminti. Reikšminiai žodžiai: metalurgijos atliekos, plieno šlakas, kelių tiesyba, asfaltas. Возможности применения стального шлака из дуговой сталеплавильной печи для производства асфальтовой смеси Резюме. В статье ставилась цель исследовать возможности применения стальных шлаков, образующихся в процессе производства стали в дуговой сталеплавильной печи (ДСП), для производства асфальтовой смеси. Исследовались физические и химические свойства шлака из ДСП. Текстура, морфология и состав стального шлака определялись с использованием оптической микроскопии, дифракции рентгеновских лучей, электронной микроскопии, энергодисперсной спектрометрии и γ-спектрометрического анализа. Образцы шлака из ДСП были взяты на заводе по производству стали в Хорватии. Геометрические, физико-механические и прочностные свойства образцов сравнивались со свойствами других шлаков (из Словении) и с натуральными материалами. Полученные результаты подтвердили возможность применения шлака исследованной стали и натурального камня для производства асфальтовой смеси. Натуральные материалы, применяемые в асфальтовых смесях при строительстве магистралей и дорог с интенсивным движением, и исследованный стальной шлак обладают приблизительно одинаковыми хорошими физико-механическими свойствами, однако шлак из ДСП более устойчив при шлифовании. При анализе большое внимание также уделялось свободным CaO и MgO, вызывающим нестабильность материала. Эти оксиды являются основным фактором, лимитирующим применение стального шлака при производстве асфальта. Ключевые слова: отходы металлургического производства, стальной шлак, строительство дорог, асфальт.